Model predictive control for parallel three‐level T‐type grid‐connected inverters in renewable power generations. Issue 11 (3rd July 2017) - Xing, Xiangyang; Zhang, Chenghui; He, Jinwei; Chen, Alian; Zhang, Zicheng
Abstract : As the penetration of renewable power generation units connected to the grid increases, high power quality and high efficiency have been widespread concerned. The parallel 3LT 2 Is are necessary to improve the quality and efficiency of applications. The use of common dc‐link without isolating transformers will cause the zero‐sequence circulating current (ZSCC) problem. This study proposes a finite control set model predictive current control to suppress the ZSCC, balance the neutral‐point (NP) voltage as well as control the currents with fast transient response. The cause of the ZSCC generated in the parallel 3LT 2 I is analysed. The proposed ZSCC suppression technique is achieved through changing the redundant small vectors in the parallel 3LT 2 Is. Moreover, the coupling problem between the ZSCC and NP balance is solved by the amplitude comparison of NP voltage and ZSCC. As a result, better ZSCC suppression and NP voltage performance can be achieved in different output currents and filter inductance condition. The proposed method has been verified experimentally.